Glutaredoxin-like protein (GLP)—a novel bacteria sulfurtransferase that protects cells against cyanide and oxidative stresses - de Paula, Carla Peres [UNESP]; dos Santos, Melina Cardoso [UNESP]; Tairum, Carlos A. [UNESP]; Breyer, Carlos Alexandre [UNESP]; Toledo-Silva, Guilherme; Toyama, Marcos Hikari [UNESP]; Mori, Gustavo Maruyama [UNESP]; de Oliveira, Marcos Antonio [UNESP] (Springer Nature, 2020)
The pathogen Xylella fastidiosa belongs to the Xanthomonadaceae family, a large group of Gram-negative bacteria that cause diseases in many economically important crops. A predicted gene, annotated as glutaredoxin-like protein (glp), was found to be highly conserved among the genomes of different genera within this family and highly expressed in X. fastidiosa. Analysis of the GLP protein sequences revealed three protein domains: one similar to monothiol glutaredoxins (Grx), an Fe-S cluster and a thiosulfate sulfurtransferase/rhodanese domain (Tst/Rho), which is generally involved in sulfur metabolism and cyanide detoxification. To characterize the biochemical properties of GLP, we expressed and purified the X. fastidiosa recombinant GLP enzyme. Grx activity and Fe-S cluster formation were not observed, while an evaluation of Tst/Rho enzymatic activity revealed that GLP can detoxify cyanide and transfer inorganic sulfur to acceptor molecules in vitro. The biological activity of GLP relies on the cysteine residues in the Grx and Tst/Rho domains (Cys33 and Cys266, respectively), and structural analysis showed that GLP and GLPC266S were able to form high molecular weight oligomers (> 600 kDa), while replacement of Cys33 with Ser destabilized the quaternary structure. In vivo heterologous enzyme expression experiments in Escherichia coli revealed that GLP can protect bacteria against high concentrations of cyanide and hydrogen peroxide. Finally, phylogenetic analysis showed that homologous glp genes are distributed across Gram-negative bacterial families with conservation of the N- to C-domain order. However, no eukaryotic organism contains this enzyme. Altogether, these results suggest that GLP is an important enzyme with cyanide-decomposing and sulfurtransferase functions in bacteria, whose presence in eukaryotes we could not observe, representing a promising biological target for new pharmaceuticals.
Keywords: Glutaredoxin (Grx); Glutaredoxin-like protein (GLP); Reactive oxygen species (ROS); Thiosulfate sulfurtransferase/Rhodanese (Tst/Rho); Xylella fastidiosa